The Impact of Authentic Materials on Reading Comprehension, Motivation, and Anxiety Among Iranian Male EFL Learners. Issue 1 (2nd January 2022) - Namaziandost, Ehsan; Razmi, Mohammad Hasan; Ahmad Tilwani, Shouket; Pourhosein Gilakjani, Abbas
Abstract: This study aimed to investigate the effect of using authentic materials on English as a foreign language (EFL) learners' reading comprehension, reading motivation, and reading anxiety. In this study, 58 Iranian male EFL learners were selected and randomly assigned to an experimental and a control group. Both groups were pretested through a reading comprehension test and the motivation for reading questionnaire (MRQ) to test their reading comprehension ability and reading motivation. Having participated in a period of 20 sessions in which the experimental group received treatment of exposure to authentic materials and control group to simplified materials, the students took a posttest of the reading comprehension test and completed the MRQ. Additionally, to test students' reading anxiety, the two groups completed Foreign Language Reading Anxiety Scale (FLRAS) in two pre- and posttest assessments. The scores obtained were analyzed using one-way analysis of covariance and paired samples t-tests. The results indicated that authentic materials enhanced Iranian learners' reading motivation and their reading comprehension ability. In addition, the findings suggested that the use of authentic texts significantly improved EFL learner's anxiety in the experimental group. The implications of the study are discussed.